Educational Management Based on Religious Moderation: Empirical Study of Practices in Pesantren - Adi Wibowo; Moh. Roqib; Subur; Zohaib Hassan Sain (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
Religious moderation has become an important concept in Islamic education, especially in Indonesia, as an effort to instill the values of balance, tolerance, and inclusiveness. Pesantren, as traditional Islamic educational institutions, have a central role in teaching moderation values to santri. This article aims to analyze the application of religious moderation in educational management in pesantren, focusing on aspects of curriculum, leadership, and character education. This research uses a qualitative method with a case study approach at Pesantren An-Nawawi Berjan Purworejo. Data were collected through observation, in-depth interviews with caregivers, santri, and teaching staff, as well as document analysis related to curriculum policies and pesantren management. The analysis was conducted using a thematic approach to identify patterns of religious moderation implementation in the daily activities of the pesantren. The results showed that the application of religious moderation in Pesantren An-Nawawi Berjan Purworejo had a positive impact on increasing tolerance among students and inclusive character building. Religious moderation is also integrated in human resource management, curriculum development, and pesantren leadership activities. In addition, the values of religious moderation help this pesantren in managing social dynamics better, increasing the operational effectiveness of the Institute. The implementation of religious moderation in Pesantren An-Nawawi shows how the pesantren can adapt to modern challenges such as intolerance and radicalism, while still maintaining its traditional identity. The integration of moderation values in the curriculum and management of pesantren strengthens the role of pesantren as institutions that educate generations that are not only academically intelligent, but also have tolerant and inclusive characters. This research confirms that religious moderation plays an important role in pesantren education management, particularly in improving tolerance and management effectiveness. The implication is that this model of implementing religious moderation can be adopted by other pesantren in Indonesia in facing the challenges of radicalism and maintaining social harmony.